Going global, veiling the poor global city imaginaries in Metro Manila - Michel, Boris (2010)
This article examines neoliberal modes of urban governance and revanchist urbanism in Metro Manila. Making Manila attractive to foreign capital, international tourism, and the new urban middle classes, as well as presenting it as a symbol of the state's attempt to transform the Philippines into a "newly industrialized country," is a vital part of a neoliberal project that gained power in the mid-1990s. On the one hand, this project seeks the erasure of marginality and poverty, which contradict the image of global modernity. On the other hand, it entails a reconstruction process beyond erasure: the shaping of specific parts of the city as a "globally competitive metropolis." To underline the argument two case studies are presented.
Keywords: Neoliberalism; Urbanization; Globalization; Privatization; Industrialization; Cities and towns; Metro Manila